INFORMATION AND COMMUNICATION TECHNOLOGIES IN INFORMATION SCIENCE: identifying data - Sant’Ana, Ricardo César Gonçalves [UNESP] (Universidade Federal do Rio Grande, 2023)
This article presents study made about the adherence of researches made in Computer Science, specially in master's dissertations, with concepts related to Information and Communication Technologies. This is an exploratory research that sought to use resources of frequency analysis and term dispersion, and of similarity between them, in order to identify traces of this adherence and to present alternatives of visualization of the data obtained by the analysis. It is concluded that the utilization of analysis and visualization resources not only allow to explicit the adherence of Information Science to terms related to Information and Communication Technologies but also allow to identify internal configurations of the research production such as characterization of line of research. It is hoped that this research will motivate the development of future papers that allow not only the uncovering of the area for its own researchers but also to the areas the Information Science has the potential of interaction.
TECNOLOGIAS DA INFORMAÇÃO E COMUNICAÇÃO NA CIÊNCIA DA INFORMAÇÃO: identificando dados
Keywords: Data Visualization; Information and Communication Technologies; Information Science; Interdisciplinarity